2020
DOI: 10.20471/acc.2020.59.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Insulin-Like Growth Factor Type 1 and Intrauterine Growth

Abstract: Insulin like growth factor 1 (IGF-1) is a regulator of intrauterine growth, and circulating concentrations are reduced in intrauterine growth-restricted fetuses. The aim of our study was to investigate the relationship between IGF-1 levels in newborns and intrauterine growth, expressed as birth weight (BW). The research was designed as a cross-sectional study. The study included 71 premature newborns, gestational age (GA) ≤33 weeks. Quantitative determination of IGF-1 was performed in the 33 rd post-menstrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…Rapid uptake of AFB1 in rat and dog prostate [548] Commercial milk is contaminated with aflatoxins; AFM1 levels rise in maize-fed cows [537- Major mineral of milk; questionable influence of dairy calcium on the prostate as circulatory calcium levels are maintained within close limits [116] derived IGF-1, constituting a major part of circulating IGF-1, is an important endocrine factor involved in a variety of physiological and pathological processes [567] . Notably, locally derived IGF-1 cannot replace liver-derived IGF-1 for the regulation of a large number of other parameters including GH secretion, cortical bone mass, and prostate size [567] .…”
Section: Fetal Prostate Growthmentioning
confidence: 99%
“…Rapid uptake of AFB1 in rat and dog prostate [548] Commercial milk is contaminated with aflatoxins; AFM1 levels rise in maize-fed cows [537- Major mineral of milk; questionable influence of dairy calcium on the prostate as circulatory calcium levels are maintained within close limits [116] derived IGF-1, constituting a major part of circulating IGF-1, is an important endocrine factor involved in a variety of physiological and pathological processes [567] . Notably, locally derived IGF-1 cannot replace liver-derived IGF-1 for the regulation of a large number of other parameters including GH secretion, cortical bone mass, and prostate size [567] .…”
Section: Fetal Prostate Growthmentioning
confidence: 99%
“…Single nucleotide polymorphisms rs2234693-rs9340799 ESR1 variants MTHFR 677C > T variant [74,75] [ [76][77][78][79] Genetic causes of preeclampsia IGF-1-insulin growth factor 1; IGF-2-insulin growth factor 2; IGFBP-3-IGF-binding protein 3; IGF1R-insulinlike growth factor receptor type 1; ET-1-endothelin 1; TNFα-tumor necrosis factor α; ESR1-estrogen receptor α; MTHFR-methylenetetrahydrofolate reductase.…”
Section: Fetal Chromosomal Aberrationsmentioning
confidence: 99%
“…During pregnancy, estrogen stimulates i.a. the activation of IGF-1 receptor, promoting fetal growth and response to different signals, such as hypoxia, hormones and nutrients [ 63 , 75 ]. Although in the last few years a lot of studies have been published concerning the potential association of methylenetetrahydrofolate reductase (MTHFR) 677C > T polymorphism with the risk of FGR and placental abruption, they didn’t bring enough evidence to support introducing MTHFR genetic testing into routine clinical practice [ 76 , 77 , 78 ].…”
Section: Maternal Fgr Causesmentioning
confidence: 99%
“…Hyperoxia can interfere with the binding of IGF-1 and its receptor, IGF-1R, affect the development of lung tissues, and subsequently hamper the normal alveolar and microvascular development, causing pathological changes similar to those seen in BPD ( 22 , 24 ). In addition, studies have shown that the serum levels of IGF-1 are associated with the risk of developing BPD ( 25 , 26 ). These studies have highlighted that IGF-1 could be used as a novel anti-BPD therapeutic target.…”
Section: Introductionmentioning
confidence: 99%